Analysis of thermal performance and drilling costs of borehole heat exchanger (BHE) in a river deposited area. (May 2020) - Luo, Jin; Zhang, Yuhao; Rohn, Joachim
Abstract: Two of major concerns to the installation of ground source heat pump system (GSHP) are linked to thermal performance and initial costs of borehole heat exchanger (BHE). In a heterogeneous field, both thermal performance and drilling costs of BHE could be varied drastically. In this paper, specific extractable heat and drilling costs of BHE in a river deposited area which contains three terraces is studied. Geological setting of the soil and rock formations was first investigated. Thermo-physical properties of the geological materials were measured to estimate the specific extractable heat of BHE. The drilling cost of BHE was determined by considering the drillability of rock and soil. Both the specific extractable heat and drilling costs of BHEs was investigated. The results show that the specific extractable heat of BHE increases from 45 W/m to 70 W/m and the drilling costs increase also from 33.7 USD/m till 79.7 USD/m from first terrace to the third terrace. Lastly, a parameter that represents the benefit-to-investment of BHE was mapped to display the thermo-economic feasibility for the BHE-based GCHPs installation of the three river terraces. Highlights: Thermal performance and drilling costs of borehole heat exchanger in a river deposited area is investigated. The thickness of Quaternary deposits very dramatically at different river terraces. Specific extractable heat and drilling costs of BHE increase with increasing the terrace order. Benefits-to-Investment ratio is mapped to show the thermo-economic feasibility of BHE installation.